Impact of fecal microbiota transplantation in dogs - Cantas, Leon; Goll, Rasmus; Fenton, Christopher G.; Paulssen, Ruth H.; Sørum, Henning (Frontiers in Veterinary Science, 2025)
BackgroundThe digestive tract hosts a variety of microorganisms. These microorganisms “micro-organs” play multiple crucial roles in physiological, immunological, and metabolic processes in the body. The manipulation and transplantation of “micro-organs” have lately gained increasing interest in human medicine with promising clinical outcomes, whereas much less is known in veterinary practice.ObjectivesThe goals of this pilot study were to evaluate the safety and impact of Fecal Microbiota Transplantation (FMT) for dogs suffering from non-infectious digestive disorders.AnimalsSeven client-owned adult dogs with idiopathic persistent diarrhea (>3 weeks) and very poor skin-coat conditions received the intervention (FMT) and were evaluated in a private veterinary clinic.MethodsTransplants have been taken from healthy donors and were administered rectally to recipients. Objective clinical examinations with analyses of blood and feces samples on day 0 (pre-FMT) and days 14–28 (post-FMT) were performed. Besides the conventional blood hematology and biochemistry analyses, 16S rRNA sequencing analysis was used in fecal samples.ResultsNo FMT-related complications occurred. Five of seven (71%) patients demonstrated improved fecal parameters associated with better overall clinical outcome, whereas four of the five (80%) recovered recipients showed molecular correlation with the donor gut microbiota after rectal FMT. There were insignificant changes shown for the conventionally analyzed blood samples. The serum cobalamin levels showed a tendency to increase in recovered recipients.ConclusionFMT was easy to apply and displayed certain health benefits in this study. Our findings reveal the important role of a “re-gained” gut microbiome balance in the overall health of dogs. Further research is needed to identify the dynamics and interplay between the different bacterial phyla that may have an impact on the stimuli of host immunologic and metabolic responses.